Ultrastructural analysis of zinc oxide nanospheres enhances anti-tumor efficacy against Hepatoma - Hassan, Amr; Al-Salmi, Fawziah A.; Abuamara, Tamer M. M.; Matar, Emadeldin R.; Amer, Mohamed E.; Fayed, Ebrahim M. M.; Hablas, Mohamed G. A.; Mohammed, Tahseen S.; Ali, Haytham E.; Abd EL-fattah, Fayez M.; Abd Elhay, Wagih M.; Zoair, Mohammad A.; et al. (Frontiers in Oncology, 2022)
Zinc oxide nanomaterial is a potential material in the field of cancer therapy. In this study, zinc oxide nanospheres (ZnO NSs) were synthesized by Sol-gel method using yeast extract as a non-toxic bio-template and investigated their physicochemical properties through various techniques such as FTIR, XR, DLS, and TEM. Furthermore, free zinc ions released from the zinc oxide nanosphere suspended medium were evaluated by using the ICP-AS technique. Therefore, the cytotoxicity of ZnO nanosphere and released Zn ions on both HuH7 and Vero cells was studied using the MTT assay. The data demonstrated that the effectiveness of ZnO nanospheres on HuH7 was better than free Zn ions. Similarly, ZnO-Ns were significantly more toxic to HuH7 cell lines than Vero cells in a concentration-dependent manner. The cell cycle of ZnO-ns against Huh7 and Vero cell lines was arrested at G2/M. Also, the apoptosis assay using Annexin-V/PI showed that apoptosis of HuH7 and Vero cell lines by ZnO nanospheres was concentration and time-dependent. Caspase 3 assay results showed that the apoptosis mechanism may be intrinsic and extrinsic pathways. The mechanism of apoptosis was determined by applying the RT-PCR technique. The results revealed significantly up-regulated Bax, P53, and Cytochrome C, while the Bcl2 results displayed significant down-regulation and the western blot data confirmed the RT-PCR data. There is oxidative stress of the ZnO nanosphere and free Zn+2 ions. Results indicated that the ZnO nanosphere and free Zn+2 ions induced oxidative stress through increasing reactive oxygen species (ROS) and lipid peroxidation. The morphology of the HuH7 cell line after exposure to ZnO nanosphere at different time intervals revealed the presence of the chromatin condensation of the nuclear periphery fragmentation. Interestingly, the appearance of canonical ultrastructure features of apoptotic nuclei, Furthermore, many vacuoles existed in the cytoplasm, the majority of which were lipid droplets, which were like foamy cells. Also, there are vesicles intact with membranes that are recognized as swollen mitochondria.